PENGARUH PDRB, PENDIDIKAN, KESEMPATAN KERJA, DAN PERSENTASE PENDUDUK SEKTOR INFORMAL TERHADAP KEMISKINAN DI PROVINSI BALI - I Ketut Sudibia, Mohammad Iqraam, (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 6 (2020): VOL 9 NO 6, JUNI 2020, PP 1200-1430, 2020)
Poverty has become a complex and chronic problem both at the international, national and regional levels, so that mitigation requires appropriate and sustainable strategies. The purpose of this study was to determine the effect of GDP, education, employment opportunities, and the percentage of the population in the informal sector on poverty in Bali Province, both simultaneously and partially. This research was conducted in Bali Province using secondary data obtained from the Central Bureau of Statistics of Bali Province . The method of data collection used is non-participant observation. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis it was found that GRDP, education, employment opportunities and the percentage of the population in the informal sector had a simultaneous effect on poverty in the Province of Bali. Partially the GRDP has a positive and not significant effect on poverty in Bali Province, and the percentage of the population in the informal sector has a negative and not significant effect on poverty in the Province of Bali. Meanwhile, partially education and employment opportunities have a negative and significant effect on poverty in Bali Province. Keywords : Poverty, employment opportunities, education